Reperfusion Injury with Compartment Syndrome Following Systemic Thrombolysis for Cardiac Catheterization-Related Arterial Thrombosis in an Infant - Zhang, Dyan Zhewei; Tan, Teng Hong; Wong, Kenneth Pak Leung; Sundaraghavan, Sreekanthan; Choo, Jonathan Tze Liang (Journal of Pediatric Intensive Care, 2020)
Systemic thrombolysis is increasingly used for management of arterial thrombosis following cardiac catheterization, and complications apart from bleeding manifestations are not well reported. We report the case of an infant with lower limb ischemia secondary to femoral arterial thrombosis, which developed after cardiac catheterization. Systemic thrombolysis resulted in successful reperfusion of the lower limb. However, the infant subsequently developed compartment syndrome, requiring an emergent fasciotomy. This case highlights the importance of surveillance for the development of reperfusion injury-related compartment syndrome postsystemic thrombolysis for arterial thrombosis.
Keywords: reperfusion injury; compartment syndrome; thrombolysis